Hydrogel – a cutting edge delivery system for a natural wound healing promoter - Ab. Hadi, Hazrina (2019)
When the skin is injured, it would compromise the immune system as well as body’s homeostasis. Wound that fail to progress into the normal stage of healing is being recognized as delayed acute wound and chronic wound that could worsen the body condition. Honey is a well established treatment for wound healing due to its antimicrobial, antioxidants, anti-inflammatory and high sugar contents. Hence, honey based hydrogel formulation was developed and characterized. Response surface model (RSM) which consist of factorial design and central composite design was used to develop and optimized the hydrogels. Then, the characterization of the formulation was studied in term of hydrophilicity, polymerization, water vapor transmission rate (WVTR), rheological, drug release, microbial limit test, antimicrobial, stability and interaction between honey and the excipient by using Attenuated Total ReflectanceFourier Transform Infrared (ATR-FTIR). Hydrogel formulation containing polyvinyl alcohol (PVA), polyethylene glycol, agar and honey displayed a good reaction towards the selected response. Besides that, the developed hydrogel has a good hydrophilicity property, which could provide a good moisturizing condition to the wound. The hydrogel containing honey also exhibited a good WVTR where the value is lower than control formulation. A higher WVTR cause the wound to dry rapidly. Meanwhile, in rheological properties, hydrogel containing honey displayed a clear LVR line while in ATR-FTIR test, there was no substantial interaction observed in comparison with blank hydrogels. In addition, the release profile of the developed honey hydrogel followed diffusion-controlled mechanism where the delivery of the honey in consistently throughout the time. Then, in term of microbial activity, the developed formulation also exhibited a good antimicrobial property and free from pathogenic microorganism. For in vivo study, the blank and honey hydrogels did not cause irritation on the skin of the rabbit. The healing in honey hydrogels treated group was significantly faster than no treatment group as shown in wound closure percentage and histological assessment. In honey hydrogels treated group, the amount of collagen deposited is abundant and the structure of fibroblast is well organized, this indicating at the end of the animal study, the wound has entered the remodelling phase compared with the no treatment group that still in proliferation phase. Based on all of these results, there are a lot of promising properties of stingless bee honey-based hydrogels such as good hydrophilicity, elasticity, microbial safety, reliable release profile as well as efficacy in wound healing treatment.